A new species of Malayopotamon Bott, 1968 (Crustacea: Decapoda: Brachyura: Potamidae), a freshwater crab from northern Sumatra, Indonesia - Ng, Peter K.l. (Zootaxa, 2014)
A new species of potamid freshwater crab, Malayopotamon weh sp. nov., is described from the island of Pulau Weh off northern Sumatra, Indonesia. The species superficially resembles three Sumatran species: M. batak Ng & Wowor, 1991, M. tobaense (Bott, 1968), and M. turgeo Ng & Tan, 1999, but can easily be distinguished by various carapace as well as gonopod characters.